In silico analysis of mismatches in RT-qPCR assays of 177 SARS-CoV-2 sequences from Brazil - Santos, Renan da Silva (Rev Soc Bras Med Trop, 2020)
INTRODUCTION: Quantitative reverse transcription polymerase chain reaction (RT-qPCR) can detect the severe acute respiratory syndrome Coronavirus-2 (SARS-CoV-2) in a highly specific manner. However, a decrease in the specificity of PCR assays for their targets may lead to false negative results. METHODS: Here, 177 high-coverage complete SARS-CoV-2 genome sequences from 13 Brazilian states were aligned with 15 WHO recommended PCR assays. RESULTS: Only 3 of the 15 completely aligned to all Brazilian sequences. Ten assays had mismatches in up to 3 sequences and two in many sequences. CONCLUSION: These results should be taken into consideration when using PCR-based diagnostics in Brazil.